Amphiphilic polymer conetworks with defined nanostructure and tailored swelling behavior for exploring the activation of an entrapped lipase in organic solvents. (1st May 2015) - Sittko, Ina; Kremser, Kathrin; Roth, Meike; Kuehne, Stefanie; Stuhr, Susan; Tiller, Joerg C.
Abstract: Amphiphilic polymer conetworks (APCNs) are nanomaterials that greatly activate entrapped enzymes in organic solvents. We have designed two novel APCNs with similar nanostructure, but different swelling behavior in toluene and n -heptane to explore the true origin of enzyme activation. They were realized by copolymerization of telechelic methacrylamide terminated poly(2-methyl oxazoline) (PMOx) with butyl acrylate (BuAc) and 2-ethylhexyl acrylate (EhAc), respectively. While the first APCN swells in toluene but not in n -heptane, the latter swells in both solvents. Lipase Cal B entrapped in the conetworks is most active at a composition that contains some 50 wt% PMOx in all cases. Further, the maximal activation of Cal B with respect to the suspended powder is some 20-fold independent on the solvent as long as the APCN is swellable. Graphical abstract: Highlights: Amphiphilic polymer conetworks activate inserted lipase in organic solvents. The activation is due to the nanophasic structure. If the organic phase swells separately relative activation is solvent independent.